Geometric measure theory and minimal surfaces lectures given at the Centro internazionale matematico estivo (C.I.M.E.) held in Varenna (Como), Italy, August 25-September 2, 1972 - Bombieri, Enrico 1940- (CIME summer schools, 2011)
W.K. ALLARD: On the first variation of area and generalized mean curvature.- F.J. ALMGREN Jr.: Geometric measure theory and elliptic variational problems.- E. GIUSTI: Minimal surfaces with obstacles.- J. GUCKENHEIMER: Singularities in soap-bubble-like and soap-film-like surfaces.- D. KINDERLEHRER: The analyticity of the coincidence set in variational inequalities.- M. MIRANDA: Boundaries of Caciopoli sets in the calculus of variations.- L. PICCININI: De Giorgi?s measure and thin obstacles.